PERAN GURU PPKN DALAM MENINGKATKAN NILAI MORAL SISWA KELAS VIII A DI SMP NEGERI 2 DAMPAL SELATAN - Erni Nurdin; Rosdiana Rosdiana (Scolae: Journal of Pedagogy, 2025)
This study aimed to analyze the role of Civic Education teachers in improving the moral values of eighth-grade students at SMP Negeri 2 Dampal Selatan and to identify the supporting and inhibiting factors in its implementation. This study employed a descriptive qualitative approach. The research informants consisted of the principal, a Civic Education teacher, and eighth-grade students. Data were collected through observation, interviews, and documentation. Data analysis involved data reduction, data presentation, and conclusion drawing. The results showed that Civic Education teachers played important roles as directors, mentors, role models, and monitors in improving students' moral values. Teachers provided advice and guidance concerning norms and school regulations, mentored students experiencing behavioral problems, demonstrated positive behavior, and monitored students' conduct within the school environment. The moral values developed included religiosity, discipline, honesty, responsibility, tolerance, social concern, and respect for others. Supporting factors included school facilities, students' personal data, and the school's character-building program. Inhibiting factors included students' individual conditions, family and social environments, technological developments, and limited cooperation among teachers. The findings indicate that improving students' moral values requires role modeling, habituation, guidance, monitoring, and cooperation among all members of the school community.